2003
DOI: 10.1001/jama.289.4.454
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Impact of Financial Conflicts of Interest in Biomedical Research

Abstract: Dr Gross has served as a consultant and scientific advisory board member to Astra-Zeneca. Mr Bekelman has served as a consultant to Turbogenomics Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
1,053
13
97

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,658 publications
(1,190 citation statements)
references
References 86 publications
27
1,053
13
97
Order By: Relevance
“…[20,21] Besides, if a trial is funded by the industry, its results could be biased in favor of the sponsor [22,23].…”
Section: Reporting Of Items Related To Biases In Rctsmentioning
confidence: 99%
“…[20,21] Besides, if a trial is funded by the industry, its results could be biased in favor of the sponsor [22,23].…”
Section: Reporting Of Items Related To Biases In Rctsmentioning
confidence: 99%
“…However, as with any financial relationships with industry, there are risks for conflicts of interest and bias [2,5,6,20,22,25,30,38,43]. As a result, increased transparency in these relationships has been stressed.…”
Section: Introductionmentioning
confidence: 99%
“…All this largesse translates into, as of 2001, 80,000 clinical trials going on in the U.S., with 2.3 million Americans having served as subjects [8]. Up to one quarter of academic investigators in biomedical research receive industry funding [9]. Accompanying this alarming statistic is that almost half of investigators received research related gifts, items definitely not integral to the research process.…”
Section: "He Who Would Do a Great Evil Must First Of All Convince Himmentioning
confidence: 99%
“…And finally, a recent meta-analysis of eight articles, that together compiled a total of 1140 studies, showed a robust 3.6 odds ratio (95% C.I. 2.6-4.9) favoring pro-industry conclusions when sponsorship was from industry [9]. All this overwhelming data suggests that industry funding definitely creates a powerful, potential bias within the methodology of any clinical research trial.…”
Section: "He Who Would Do a Great Evil Must First Of All Convince Himmentioning
confidence: 99%
See 1 more Smart Citation